Criticism of science on the moral of the company - Armando-Pizarro, Alejandro (2019)
The relationship between scientific progress and moral progress, the contradictory nature of that relationship, and the question of how to resolve these contradictions, is one of the philosophical and social problems of our time. The great French philosopher Jean Jacques Rousseau, is the first to explain the negative influence of science on the moral state of society. His views were paradoxical in various aspects of social progress, however testified to the deep philosophical insight of the great French thinker. Karl Marx was the first to give a scientific explanation of the root causes of contradiction between scientific progress and moral evolution of capitalist society.